Intellectual Capital Disclosure and The Underpricing Of Indonesian Initial Public Offerings - Utami, Elok Sri; Illiyyin, Nurul; Gumanti, Tatang Ary (Jurnal Akuntansi dan Bisnis, 2019)
Studies examining the relationship between the level of intellectual capital and firm values of public companies have been mounting. Yet, very view is devoted on those that are making initial public offering (IPO). For already publicly companies, intellectual capital disclosure can be seen in the annual report. For IPO, the information is embedded in the prospectuses. This study is aimed to analyze the influence of intellectual capital disclosure index (ICDI) and other variables including the prestige of underwriter, financial leverage, return on assets (ROA), and firm size on the extent of underpricing of companies making IPO from 2013 to 2017. The population consist of 125 companies. A total of 79 IPOs satisfied the sample selection criteria. Results using multiple linear regression analysis show ICDI, the prestige of underwriter, and company size have negative and significant effect on the level of underpricing. Whilst, financial leverage and profitability (ROA) are not the explanatory variables for the variation of underpricing. Penelitian yang menguji hubungan antara tingkat modal intelektual dan nilai-nilai perusahaan-perusahaan publik telah meningkat. Namun demikian, jumlah penelitian yang ada masih sangat dikhususkan untuk menguji perusahaan yang melakukan penawaran umum perdana (initial public offerings = IPO). Untuk perusahaan yang sudah terbuka, pengungkapan modal intelektual dapat dilihat dalam laporan tahunan. Untuk IPO, informasi tersebut tersedia di dalam prospektus. Penelitian ini bertujuan untuk menganalisis pengaruh indeks pengungkapan modal intelektual (ICDI) dan variabel-variabel lain termasuk underwriter prestige, financial leverage, return on assets, dan ukuran perusahaan terhadap tingkat underpricing perusahaan yang melakukan IPO dari 2013 hingga 2017. Populasi penelitian terdiri atas 125 perusahaan. Sebanyak 79 IPO memenuhi kriteria pemilihan sampel. Hasil analisis menggunakan regresi linier berganda menunjukkan ICDI, underwriter prestige, dan ukuran perusahaan berpengaruh negatif dan signifikan terhadap tingkat underpricing. Sementara, financial leverage, dan profitabilitas (ROA) bukan variabel penjelas untuk variasi underpricing.